Verwaltete Verwandtschaft Eheverbote, kirchliche und staatliche Dispenspraxis im 18. und 19. Jahrhundert - Lanzinger, Margareth (2015)
This study analyses the phenomenon of marriages between kin in the various relevant discursive and conceptual, legal and political, administrative and bureaucratic, familial and household-organizational, sociocultural and sociopolitical contexts. These were interwoven so as to lead all the way from villages and local parishes to the Roman Curia, and from widower's households and local municipal offices to the Imperial Court Chancellery in Vienna. The focus on how kinship was administrated opens up an approach to processes by which the state and the church, as well as the state and the regions, were integrated during an era that, in this respect, would prove to be historically decisive.